Role of Social Media in Leveraging Urban Community Empowerment - Ester Betseba, Gita Aprinta; Triastuti, Endah (Jurnal The Messenger, 2022)
Introduction: This study tries to explores the significant roles of Twitter in creating leverage community participation as part of community empowerment in urban context. Twitter’s characters encourage people to informalize current issue in easy digestive forms. This study argues that Twitter practice will improve urban community for better life in every aspects. Also this study focusing on how urban community utilize Twitter to participate in city issues.Methods: This research used several data collection and processing including online data mining through Netlytic, online observation and semi structured interview within time period from 2021–2022.Findings: The research’s finding portrayed results in three achievements. First, Twitter significantly created leverage empowerment in a form of community participation to improve the city quality of life. Second, community empowerment was gained through holistic process and come. Third, using Twitter as appropriated and integrated strategy is a design of community empowerment. Twitter, in particular #laporhendi can be alternatives space for community discussion and participation amongst residents and local government and lead to community empowerment. Practically, urban community has the same opportunity to access Twitter and creates dynamically interaction and communication in Twitter in many direction, one to one ways, or two ways.Originality: Although research about social media and community empowerment has been studied for decades, many research tends to explore and focus on rural and marginal community. There were few studies emphazise and discusses from the urban community point of view.